Exploring effects of chickpea-derived crude oligosaccharides on gut microbiota and their potential in cashew nut yogurt-like product development - Orawan La-ongkham; Kanthida Wadeesirisak; Sudathip Chantorn (Applied Food Research, 2025)
The increasing use of prebiotics in food products has heightened interest in their potential as dietary supplements to enhance gut microbiota composition and improve digestive health. While fructooligosaccharides (FOS) are among the most extensively studied prebiotics, recent attention has also been directed toward raffinose family oligosaccharides (RFOs) from chickpeas due to their emerging prebiotic potential. This study evaluated the prebiotic effects of crude oligosaccharides extracted from two chickpea varieties—Kabuli and Desi— on gut microbiota composition and metabolite production using an in vitro simulated gut microbiota model. Crude oligosaccharides from Kabuli (COK) and Desi (COD) chickpeas were extracted using 50 % ethanol at a 1:5 (w/v) ratio for 60 min, yielding oligosaccharide contents of 27.12 and 24.93 mg/mL, respectively. High-performance anion exchange chromatography with pulsed amperometric detection analysis identified raffinose, stachyose, and verbascose in both COK and COD. Then, an in vitro simulated gut microbiota fermentation system was used to investigate the prebiotic effects of crude oligosaccharides from the two chickpea varieties on the gut microbiota composition and their metabolites. Based on the results, COK and COD promoted the growth of beneficial gut bacteria, including Megamonas, Phascolarctobacterium, Streptococcus, Enterococcus, Selenomonadaceae, and Escherichia coli. COK fermentation resulted in the highest production of short-chain fatty acids. Furthermore, cashew nut yogurt-like product supplemented with 2–10 % COK or COD maintained stable physicochemical properties and sustained lactic acid bacteria and Bifidobacterium spp. over 14 days of storage at 4 °C, suggesting the potential for developing functional food products.